Natural Bioactive Compounds As Protectors Of Mitochondrial Dysfunction In Cardiovascular Diseases And Aging - Arauna, Diego; Furrianca Llaneza, Maria Cristina; Espinosa Parrilla, Maria Yolanda; Fuentes, Eduardo; Alarcon, Marcelo; Palomo, Ivan (My University, 2019)
Diet, particularly the Mediterranean diet, has been considered as a protective factor against the development of cardiovascular diseases, the main cause of death in the world. Aging is one of the major risk factors for cardiovascular diseases, which have an oxidative pathophysiological component, being the mitochondria one of the key organelles in the regulation of oxidative stress. Certain natural bioactive compounds have the ability to regulate oxidative phosphorylation, the production of reactive oxygen species and the expression of mitochondrial proteins; but their efficacy within the mitochondrial physiopathology of cardiovascular diseases has not been clarified yet. The following review has the purpose of evaluating several natural compounds with evidence of mitochondrial effect in cardiovascular disease models, ascertaining the main cellular mechanisms and their potential use as functional foods for prevention of cardiovascular disease and healthy aging.
Keywords: cardiovascular diseases; aging; natural compounds; mitochondria